Risperidone and Carbamazepine Combination in Treatment of Klüver-Bucy Syndrome: A Case Report - Hamed, AlJadani Ahmed (Scientific Journal of Medical Research, 2019)
Klüver-Bucy (KBS) syndrome is a rare neurobehavioral disorder, characterized by hypersexuality, hyperphagia, hyper-orality, visual agnosia and placidity. Here I present a case of A-21-year-old Saudi female with a Kluver-Bucy syndrome secondary to left unilateral parieto-temporal tumor resection who responded to a combination of carbamazepine and risperidone.